2015
DOI: 10.1563/aaid-joi-d-13-00097
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Low-Level Laser on Osseointegration Around Machined and Sandblasted Acid-Etched Implants: A Removal Torque and Histomorphometric Analyses

Abstract: Evaluation of the influence of laser application on osseointegration around implants with different surface characteristics is limited. This study aims to evaluate the influence of low-level lasers on the early stages of osseointegration. Ninety-six external hex implants (3.75 mm × 5.0 mm) were placed in 24 rabbits-one machined and one sandblasted acid-etched per tibia. The rabbits were later divided into the laser group, which received a total dose of 24 J/cm(2) of gallium-aluminum-arsenide laser over 15 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This study focused on assessing outcomes at specific and clinically relevant intervals, indicating it is important to keep in mind that previous research on photobiomodulation in dental implantology has also yielded promising results; however, those studies either used different surface-treated implant systems or assessed outcomes at different or less relevant intervals [16][17][18]. It is also worth noting that a few studies [13,[19][20][21] have shown conflicting or negative results, indicating that the effectiveness of LLLT may vary based on individual patient factors and other variables. Despite this, this study contributes to the prevailing consensus among the majority of studies, leaning toward LLLT being beneficial in enhancing dental implant stability outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on assessing outcomes at specific and clinically relevant intervals, indicating it is important to keep in mind that previous research on photobiomodulation in dental implantology has also yielded promising results; however, those studies either used different surface-treated implant systems or assessed outcomes at different or less relevant intervals [16][17][18]. It is also worth noting that a few studies [13,[19][20][21] have shown conflicting or negative results, indicating that the effectiveness of LLLT may vary based on individual patient factors and other variables. Despite this, this study contributes to the prevailing consensus among the majority of studies, leaning toward LLLT being beneficial in enhancing dental implant stability outcomes.…”
Section: Discussionmentioning
confidence: 99%